Cratylia argentea – review of a tropical shrub legume: Biology and agronomy - Schultze-Kraft, Rainer; Lascano, Carlos E (International Center for Tropical Agriculture, 2024)
A comprehensive review, based on about 170 references, synthesizing research and development about Cratylia argentea, is presented to contribute to expand interest in its diffusion and use in animal production systems. The species has been widely evaluated, mainly in tropical America, with the objective to develop a shrub legume as an alternative to the fertile soils requiring Leucaena leucocephala and Gliricidia sepìum. The review comprises: (1) an illustrated description of the species, its biogeography and information on germplasm collections and genetic diversity; (2) synthesis and discussion of results from agronomic research, reproductive biology and seed production; (3) synthesis and discussion of results from research on nutritive value including secondary compounds, forage utilization and animal production. Particular strengths of the species are adaptation to the acid, low-fertility soils that prevail in the tropics, drought tolerance in subhumid climates with a pronounced dry season, and high nutritive value leading to increased animal production. Major shortcomings are slow establishment, labor demand in cut-and-carry systems and rapidly declining seed quality. A blend of two germplasm accessions was released as a commercial forage legume cultivar in Costa Rica and Colombia. Technology adoption issues are discussed and suggestions for future research presented.